IbM : Petani Pisang Rutai di Kabupaten Kutai Kartanegara - Purwati Purwati (Lembaga Penelitian dan Pengabdian Masyarakat, 2017)
Rutai banana plant is one of some indegenous plant from East Kalimantan. Rutai banana plant is a plant that comes from the local Kutai regency. The existence of banana plants in the garden rutai farmers are increasingly rare, because the plant is not cultivated on a large scale. Efforts have been made by the Local Government is to declare a banana as an appetizer rutai mandatory in aquatic mammal. But the program has not been coupled with the dissemination of banana cultivation techniques rutai through field sanitationThe method used in the application of science and technology for the Community is involved in activities rutai banana growers.The impact of the application of science and technology for the People that use rutai healthy banana seeds can increase crop productivity and prevent pests and fusarium wilt disease . Evaluation and development of post- plant demonstration plots conducted every 1 months by the implementation team.